2020
DOI: 10.1021/acs.jafc.9b06046
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Usability of Pea Protein Isolate in Food Applications through Modifying Its Structural and Sensory Properties via Deamidation by Glutaminase

Abstract: This study aimed to demonstrate the feasibility of improving the properties of pea protein isolate (PPI) related to food applications via deamidation with glutaminase. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Fourier transform infrared (FT-IR) profiling revealed that the current glutaminase treatment did not change the basic protein subunit composition. However, it allowed a certain extent of protein unfolding and conformational reorganization to generate more flexible and exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 36 publications
(93 reference statements)
4
45
0
Order By: Relevance
“…Our recent research 21b found that the isoelectric point of seabuckthorn seed protein occurred at pH 5.0 (PI), which explains the lowest PS around pH 5 in this study. The increase of PS at pH values > PI was also reported by Fang et al 27 It was anticipated that the reduction in the phytic acid content by the phytase treatment could increase the solubility of seabuckthorn seed proteins, as a similar result was observed in faba bean flour protein. 19 In vitro digestibility of SSR-3h and ESSR-3h samples During the 4 h gastric digestion, the digestibility of ESSR-3h (ESSR-G: from 49.82% to 55.84%) was significantly (P < 0.05) higher than that of SSR-3h (SSR-G: from 43.61% to 48.49%) (Fig.…”
Section: Wileyonlinelibrarycom/jsfasupporting
confidence: 78%
“…Our recent research 21b found that the isoelectric point of seabuckthorn seed protein occurred at pH 5.0 (PI), which explains the lowest PS around pH 5 in this study. The increase of PS at pH values > PI was also reported by Fang et al 27 It was anticipated that the reduction in the phytic acid content by the phytase treatment could increase the solubility of seabuckthorn seed proteins, as a similar result was observed in faba bean flour protein. 19 In vitro digestibility of SSR-3h and ESSR-3h samples During the 4 h gastric digestion, the digestibility of ESSR-3h (ESSR-G: from 49.82% to 55.84%) was significantly (P < 0.05) higher than that of SSR-3h (SSR-G: from 43.61% to 48.49%) (Fig.…”
Section: Wileyonlinelibrarycom/jsfasupporting
confidence: 78%
“…Chemical modification was also applied for improving the properties of pea proteins. Deamidation with glutaminase of pea protein isolates does not change the basic protein composition but enables its unfolding and conformational reorganization (Fang, Xiang, Sun-Waterhouse, Cui, & Lin, 2020). The deamidation leads to pea proteins with higher flexibility, solubility, homogeneity and dispersibility with reduced beany flavor, grittiness, and lumpiness compared to those of the untreated.…”
Section: Post-processing: For a Better Functionality And Sensory Percmentioning
confidence: 99%
“…The deamidation leads to pea proteins with higher flexibility, solubility, homogeneity and dispersibility with reduced beany flavor, grittiness, and lumpiness compared to those of the untreated. Thus, the glutaminase treatment offers a promising approach for enhancing the applicability of pea proteins (Fang et al, 2020).…”
Section: Post-processing: For a Better Functionality And Sensory Percmentioning
confidence: 99%
“…Currently, health-conscious consumers demand a significant increase of plant proteins consumption compared to those from animals and, consequently, an overproduction of plant proteins [5]. In line with this trend, chia is an important source of high-quality protein (19-27%), greater than traditional foods such as rice (5.95%), wheat (9.61%) and oats (13.15%) [2] and similar to other seeds used for the generation of protein isolates such as hemp [6], peas, and chickpeas [5]. Protein isolates are high-quality food ingredients with protein contents close to 90%, which can improve both the nutritional composition and techno-functional characteristics of foods.…”
Section: Introductionmentioning
confidence: 99%